Crafting traps with attractant alcoholics an alternative for monitoring and control of borer coffee, Hypothenemus hampei (Ferrari 1867) - Agramont Richard; Cuba Nicanor; Beltrán José Luis; Almanza Juan Carlos; Loza-Murguia Manuel (Journal of the Selva Andina Research Society, 2010)
The necessity to incorporate an alternative, for monitoring and control of the borer coffee, Hypothenemus hampei (Ferrari) (Choleoptera: Curculionidae) to be feasible for the use of the coffee producers, in the community Choro, Coripata municipality, second section of Nor Yungas province, La Paz Bolivia. It was evaluated the capture of adult borer coffee individuals using 45 traps into 1,5 hectares distributed at random with four repetitions. It was used three types of craft traps, built with disposable plastic bottles of soft drinks, with the traps Casera, Brocap and Yessica, were evaluated three treatments: mixture of alcohols methyl (M) and ethylic (E) in proportions 3:1; mix 1:1 of (M) and (E); mix 1:1:1 of (M) (E) and coffee fresh cherry liquated (CFCL) and water as a witness. The largest captures of adult individuals, were present in the crafting traps with mixture of (M)(E) 3:1 with overalls (± standard deviation) adults/traps/ten days of 3414,5±3227,7 being superior to the other treatments. The crafting trap is one of the alternatives for the control and monitoring of the borer in the coffee plantations. The use of crafting traps with alcoholic attractants for the capture of adult individuals, is present as a low cost alternative, being feasible the successful use by the producers into the management integrated programs.